Analysis of The Need for Developing PJOK Modules Containing Traditional Games - Jannah, Ana Naimatul; Citrawati, Tyasmiarni (Universitas Trunojoyo Madura, 2024)
The purpose of this research is to analyze the need for developing PJOK modules that incorporate traditional games. This research uses a descriptive qualitative method oriented towards product development. The subjects of this research are 12 teachers and 188 students. Research data were obtained from the completion of observation sheets and questionnaires regarding the needs of teachers and students for the development of PJOK modules incorporating traditional games in elementary schools. The result of this research is the need for a PJOK module based on traditional games, viewed from the aspects of regional potential, student interest, environmental availability, learning objectives, and the necessity of supporting modules.